Professional graduate programs: History, objectives, and tendencies - Philippe Drumond Vilas Boas Tavares; Cezar Luiz De Mari; Lucídio Bianchetti (Arizona State University, 2021)
In the present article we approach the professional postgraduate program (PPG), bringing some elements of the origin, history, and challenges to its implementation. Focus will be given on the professional master's degree. Since it includes both academic PG and in-service training, it met a series of demands that were addressed at this level of education, especially PG lato sensu.  It is a documental study, based on the literature produced since 1996, which discuss all the regulations, and implementation aspects of the PPG within the scope of CAPES, INEP, MCTI and CNPq. The research data were analyzed from a critical perspective through data triangulation, aiming to explain the meaning of the professional PPG. In the scope of postgraduate programs (PPG), depending on their financing policies, this new modality is similar to academic PG, with the prospect of overcoming it.